Accounting for Crimmigration: A Theoretical Expansion of the Victim-Offender Overlap Framework Using a Sample of Unauthorized Foreign Nationals - Caraballo, Krystlelynn (Victims & offenders, 2025)
The criminalization of immigration (i.e. crimmigration) has complicated who constitutes an “offender” for foreign nationals lacking authorization to be in the United States (U.S.). This study proposes a theoretical expansion of the Victim-Offender-Overlap framework to account for the effect of crimmigration on the schism between “status” and “criminal” offending using 2011 survey data from 333 unauthorized individuals in Immigration and Customs Enforcement custody. These individuals were asked about their migration, U.S.-based criminality and victimization. Latent class analysis is employed to identify unique profiles among this sample. The discussion explores the theoretical and policy implications for criminological research using “unauthorized” populations.